2022
DOI: 10.1038/s41380-022-01631-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy in Alzheimer’s disease: Molecular defects and therapeutic approaches

Abstract: Mitochondrial dysfunctions are central players in Alzheimer’s disease (AD). In addition, impairments in mitophagy, the process of selective mitochondrial degradation by autophagy leading to a gradual accumulation of defective mitochondria, have also been reported to occur in AD. We provide an updated overview of the recent discoveries and advancements on mitophagic molecular dysfunctions in AD-derived fluids and cells as well as in AD brains. We discuss studies using AD cellular and animal models that have unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 115 publications
0
72
0
Order By: Relevance
“…According to the mitochondrial cascade hypothesis, these organelles are suggested to mediate or possibly even initiate pathological molecular cascades in AD. It has been reported that GIIA expression is increased in affected tissues [ 8 ] and that nerve cell death is preceded by the degeneration of the mitochondria [ 11 ]. Similar mitochondrial degeneration was reported when the nerve cells were exposed to snake venom β-neurotoxic GIIAs [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the mitochondrial cascade hypothesis, these organelles are suggested to mediate or possibly even initiate pathological molecular cascades in AD. It has been reported that GIIA expression is increased in affected tissues [ 8 ] and that nerve cell death is preceded by the degeneration of the mitochondria [ 11 ]. Similar mitochondrial degeneration was reported when the nerve cells were exposed to snake venom β-neurotoxic GIIAs [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…GIIA secreted by reactive astrocytes around the amyloid plaques in an AD brain has been shown to regulate the processing of the amyloid precursor protein in neuronal cells [ 9 , 10 ]; however, no other clear evidence about the involvement of GIIA in AD is currently available. Mitochondrial dysfunctions are central players in AD [ 11 ]. In AD brains, the mitochondria degenerate, as they do when nerve cells are intoxicated by the presynaptic neurotoxic snake venom sPLA 2 s (β-neurotoxins).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in mitophagy have been reported to lead to a gradual accumulation of defective mitochondria in AD [107]. In detail, an unbalanced increase in ROS levels occurs under AD conditions, together with a lowering of antioxidant mechanisms, which eventually causes OS.…”
Section: Defective Mitophagy In Admentioning
confidence: 99%
“…Aβ may induce mitochondrial dysfunction in AD in many ways ( Figure 8 ): (i) impairment of membranes and inhibition of mitochondrial enzymes, such as respiratory complexes, leading to decreased ATP production and increased ROS generation; inhibition of oxoglutarate dehydrogenase complex (OGDC, or α-ketoglutarate dehydrogenase complex), leading to changes in TCA; and interaction with 17β-hydroxysteroid dehydrogenase type 10 (HSD10, formerly known as Aβ binding alcohol dehydrogenase or ABAD), leading to enhancement of Aβ-induced cell stress [ 288 , 289 ]; (ii) increased expression of mitochondrial PPIF, leading to formation of PPIF-mPTP [ 224 , 290 ]; (iii) impairment of mitochondrial Ca 2+ buffering capacity, leading to calcium overload in the mitochondria, calcium-induced mPTP opening, inhibition of ATP production, increased ROS production, increased cytochrome c release, apoptosis, and neuronal injury; (iv) inhibition of preprotein import into mitochondria via the TIM/TOM complex [ 283 , 291 ]; (v) impairment of fusion/fission processes, mitophagy, and mitochondrial movement [ 292 ]; and (vi) decreased expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), which is a regulator of mitochondrial biogenesis [ 275 , 293 , 294 ].…”
Section: Linking the Amyloid Tau And The Mitochondrial Hypotheses Of ...mentioning
confidence: 99%